PELATIHAN PENGGUNAAN MICROSOFT WORD BAGI SISWA SMP DESA KURIPAN LOR PEKALONGAN - Hilya Diniya; Nia Amellia; Kamelia Elima'ana Mafudloh; Ria Anisatus Solikha; Hendri Hermawan Nugraha (Universitas Methodist Indonesia, 2022)
Kuripan Lor Village is one of the villages in the Pekalongan City area which is in Pekalongan Selatan District, Kuripan Yosorejo Village. Microsoft Word is one of the software that is often used both in processing words and numbers. Microsoft Word is software that must be mastered by students (junior high school students), but in reality not all junior high school students master it. This is due to the lack of proper training and lack of support for the application of Microsoft Word in schools. For this reason, a training activity was created in the context of community service, which aims to increase the knowledge and understanding of junior high school students in Kuripan Village in using Microsoft Word so that it will make it easier to do school work. The number of junior high school students who participated in this activity was 5 people. Based on the training that had been given and carried out, the results obtained were that the participants looked very enthusiastic, as evidenced by the active participants in asking questions and discussing the material with the presenters. After the activity it was also known that 70% were able to apply the use of Microsoft Word.